Upaya Multi Track Diplomacy Pemerintah Thailand dalam Menangani Permasalahan Perdagangan Manusia di Thailand pada 2015-2017 - Carolina Omega; Andika Drajat Murdani; Ganjar Widhiyoga (Indonesian Journal of Peace and Security Studies (IJPSS), 2023)
Human trafficking cases in Thailand have been around since the 1970s. Even though it has been more than three decades, cases of human trafficking in Thailand are still being found. Human trafficking is a real issue that Thailand faces every year. This study specifically discusses the efforts taken by the Thai Government in dealing with human trafficking. Human trafficking is one of the focuses in the concept of human security. The efforts made are in the form of collaboration with various sectors in the scope of the Multi Track Diplomacy concept. This research belongs to the type of qualitative research with literature study data collection techniques. Literature study due to lack of access to direct data collection, so the data used in this study is secondary data in the form of documents and publications available on the internet. After conducting the research process, the results found showed that the Thai Government carried out six of the nine lines of Multi-track Diplomacy. The six lines of cooperation synergize with each other and produce concrete actions in the Thai Government's efforts to deal with human trafficking. The cooperation carried out by the Thai Government with various related parties later became evidence of the government's seriousness in resolving this issue. The aftermath of this seriousness is in the form of 2 positions from Thailand to a Tier position in resolving the issue of human trafficking. However, the Thai government still makes the issue of human trafficking a national priority.